NEEDS ANALYSIS OF INTEGRATED DIMENSIONS OF KNOWLEDGE AND COGNITIVE PROCESS LEVEL ON CIRCULAR MOTION MATERIALS FOR PHYSICS LEARNING IN SENIOR HIGH SCHOOL - Illyyum Maryumi; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2022)
The competencies that students need from each learning in school are the increase in knowledge and changes in attitudes in line with improving their thinking processesHowever, the facts in the field, educators still find various obstacles in analyzing competencies to implement this integration, which is indicated by the description of teacher learning tools that impact the quality of student knowledge competency achievement. The purpose of this research is to produce an analysis model of the integration of the dimensions of Knowledge and Cognitive Process Levels in Circular Motion material for High School Physics Learning, which is poured into the resulting learning device products. This research is included in Research And Development (R and D) by applying the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), which is only reduced to the development stage. This study involved 6 product validators, 3 UNP Physics Education lecturers as experts, and three education practitioners from physics teachers in Pesisir Selatan Regency. The results of data analysis after product refinement obtained the percentage of device validation values generated for lesson plans, teaching materials, and evaluation instruments according to a team of experts and a team of practitioners, respectively, with final scores of 68.48 and 74.86, which are theoretically included in the valid category. Thus this product can be used in high school physics learning to get the results of the field feasibility test on the aspects of practicality and effectiveness.